Biallelic truncating variants in children with titinopathy represent a recognizable condition with distinctive muscular and cardiac characteristics: a report on five patients - Baban, Anwar; Cicenia, Marianna; Magliozzi, Monia; Parlapiano, Giovanni; Cirillo, Marco; Pascolini, Giulia; Fattori, Fabiana; Gnazzo, Maria; Bruno, Pasqualina; De Luca, Lorenzo; Di Chiara, Luca; Francalanci, Paola; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Monoallelic and biallelic TTN truncating variants (TTNtv) may be responsible for a wide spectrum of musculoskeletal and cardiac disorders with different age at onset. Although the prevalence of heterozygous TTNtv is relatively high in the general population, cardiac phenotyping (mainly cardiomyopathies, CMP) in biallelic titinopathy has rarely been described in children.We reviewed the medical records of pediatric patients with biallelic TTNtv and cardiac involvement. Clinical exome sequencing excluded pathogenic/likely pathogenic variants in major CMP genes.Results: Five pediatric patients (4 male) with biallelic TTNtv were included. Major arthrogryposis multiplex was observed in 4 patients; no patient showed intellectual disability. At cardiac level, congenital heart defects (atrial and ventricular septal defects, n=3) and left ventricular non-compaction (n=1) were reported. All patients had dilated cardiomyopathy (DCM) diagnosed at birth in 1 patient and at age 10, 13, 14, 17 years in the other 4 patients. Heart rhythm monitoring showed tachyarrhythmias (premature ventricular contractions, n=2; non-sustained ventricular tachycardia, n=2) and nocturnal first-degree atrio-ventricular block (n=2). Cardiac magnetic resonance imaging was performed in all patients and revealed a peculiar late gadolinium enhancement distribution in 3 patients. HyperCPKemia was present in 2 patients, and end-stage heart failure in 4. End-organ damage requiring heart transplantation (HT) was indicated in 2 patients, who were operated on successfully.Conclusions: Biallelic TTNtv should be considered when evaluating children with severe and early onset DCM, particularly if skeletal and muscular abnormalities are present, e.g. arthrogryposis multiplex and congenital progressive myopathy. End-stage heart failure is common and may require HT.